Latino Career Choice and Prestige: Examining Prestige, Cultural Values and Family Influence in Predicting Career Choice - (:unkn) unknown (My University, 2023)
Career choice continues to be a principal area for career development research, as finding ways to determine what contributes to career choices, and how those choices impact individuals’ micro and macro systems, informs best practices in vocational psychology. The field of vocational psychology can benefit from exploring myriad variables that may have an impact on career choice, career congruency, and persistence in the world of work; and highlighting the unique experiences and needs of diverse populations can produce new insight about different groups and people that the field should endeavor to improve. To this end, this study sought to uniquely contribute to the field of vocational psychology by being among the first to utilize certain measures with Latino/a populations; explore cultural values and family influences on career decision making and congruence; glean insight on traditional career choices and what may impact them; and address the gap in examining prestige with Latino/a populations: a potent dimension in career choice informed by social desirability, social norms, and present day attitudes about work. The Latino/a Values Scale, specifically the subscales of Cultural Pride and Familismo, was used to explore and predict career congruence in Latino/a males and females. The Family Influence Scale, specifically informational support, family expectations, financial support, and values/beliefs was used to explore and predict career congruence in Latino/a males and females. Finally, prestige was examined among Latino/a males and females in this study. While some analysis produced significant results, there were also considerable limitations to the study. However, all exploration within the analyses in this study can inform directions for future research, invite further inquiry into the dynamics between these groups and variables, and contribute to development and refinement of further measures and research questions around these topics.
Keywords: Career Choice; Career Congruence; Career Development; Cultural Values; Family Influence; Prestige